Offender rehabilitation reform in Japan: Effective cooperation between professional and volunteer probation officers - Minoura, Satoshi (International journal of law, crime and justice, 2018)
Probation programmes in Japan have drawn critical attention over the last decade for not effectively preventing recidivism and for relying too heavily on volunteers. Despite the establishment of a Council for Offender Rehabilitation Reform in 2006 and consequent legislative clarification of the roles of professional probation officers (PPOs) and volunteer probation officers (VPOs), the repeat offender rate has been increasing and the prevention of recidivism remains an urgent issue in criminal justice in Japan. At the same time, it is important to recognize that parole and probation revocation rates have dropped slightly and that recidivism rates are lower for sexual offenders who have undergone specialized treatment programmes administered by PPOs. This article considers what issues were addressed by Offender Rehabilitation Reform and examine whether further clarification of the roles of VPOs and PPOs is needed in terms of legislative status, caseload, personnel matters, and functions in the community. Finally, this article will discuss ideal roles for VPOs and PPOs in the face of changing social contexts in Japan.